2017
DOI: 10.1177/1352458517691150
|View full text |Cite
|
Sign up to set email alerts
|

Polyunsaturated fatty acids and the risk of multiple sclerosis

Abstract: Background Results from previous studies on PUFA intake and multiple sclerosis (MS) risk are conflicting. Objective To prospectively investigate the association between dietary intake of PUFA and MS risk. Methods We followed 80,920 women from Nurses' Health Study (1984–2004) and 94,511 women from Nurses' Health Study II (1991–2009) who reported on diet using a validated food frequency questionnaire every 4 years, and identified 479 incident MS cases during follow-up. We used Cox regression to estimate haza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(56 citation statements)
references
References 36 publications
2
54
0
Order By: Relevance
“…Polyunsaturated fatty acids (PUFAs) are strong immunomodulators in vitro and in animal models. Consistent with this, most, but not all, studies that measured seafood‐based sources or direct micronutrient PUFA intake found a reduced risk of MS with higher fatty fish intake, or cod liver oil supplementation . These findings should be interpreted cautiously, with inconsistencies across studies in the timing of the risk exposure, that is, during childhood, adolescence, or through adulthood.…”
Section: Cause Versus Course – Are the Risk Factors Different?mentioning
confidence: 67%
“…Polyunsaturated fatty acids (PUFAs) are strong immunomodulators in vitro and in animal models. Consistent with this, most, but not all, studies that measured seafood‐based sources or direct micronutrient PUFA intake found a reduced risk of MS with higher fatty fish intake, or cod liver oil supplementation . These findings should be interpreted cautiously, with inconsistencies across studies in the timing of the risk exposure, that is, during childhood, adolescence, or through adulthood.…”
Section: Cause Versus Course – Are the Risk Factors Different?mentioning
confidence: 67%
“…Positive correlation with synovial fluid composition and inversed correlation with pain score [291] ↓ Incidence and improved prognosis [292][293][294][295][296] ↓ Duration of morning stiffness and ↓ number of tender and swollen joints [297] Polymyositis and Dermatomyositis ↑ Skeletal muscle growth and functions [298] Sjögren Syndrome ↓ Inflammation and ↑ barrier function in the salivary glands [299,300] Systemic Lupus Erythematosus ↓ Inflammatory mediators, leukocyte chemotaxis and adhesion molecules expression [301] Antiphospholipid Syndrome ↑ Endothelial function [302] Multiple Sclerosis ↑ M2-like macrophages shift, prevented de-myelinization, promoted neuroprotection and re-myelinization ↓ incidence [303][304][305][306] Type 1 Diabetes Protection against T1DM in infants, no protective effect in older children reported [307,308]…”
Section: Rheumatoid Arthritismentioning
confidence: 99%
“…Here, the authors were unable to fully describe different types of dietary fat in relation to relapse because the questionnaire lacked sufficient detail. Notably, intake of certain types of fat like that from fish or oil sources may be particularly relevant for MS 2. Furthermore, with respect to MS, its long-term diet rather than intake on any specific day (or small number of days) that is the relevant parameter of interest.…”
Section: A Discussion Of the Role Of Diet In Disease Course In Pediatmentioning
confidence: 99%